2013
DOI: 10.5897/ajar12.1297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroquinone and copper coated urea on ammonia volatilization loss and n mineralization from tropical soil: Laboratory study

Abstract: The faster urea hydrolyses process leads to high amount of ammonia gas emission from urea fertilized fields. Coating of urea with various materials is the most successful strategy to control N losses from urea fertilized fields. A laboratory study was conducted to evaluate the effects of uncoated urea, as compare to urea coated with hydroquinone and Cu on NH 3 volatilization loss and rate of urea hydrolysis in soil. The coated urea treatments were prepared by using Cu and hydroquinone solutions with a fluidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Proven from research before, coating with semipermeable coating materials can hinder the initial absorbance and provide a steady supply of nutrients for a longer period of time (Naz and Sulaiman 2016). Coating alone can cause problems; hence inhibition of urease is brought into effect to minimize the hydrolysis rate of urea (Babar et al 2016;Nasima et al 2013;Du et al 2012) by deactivating of soil urease. A urease inhibitor that is eco-friendly and feasible is the best.…”
Section: Introductionmentioning
confidence: 99%
“…Proven from research before, coating with semipermeable coating materials can hinder the initial absorbance and provide a steady supply of nutrients for a longer period of time (Naz and Sulaiman 2016). Coating alone can cause problems; hence inhibition of urease is brought into effect to minimize the hydrolysis rate of urea (Babar et al 2016;Nasima et al 2013;Du et al 2012) by deactivating of soil urease. A urease inhibitor that is eco-friendly and feasible is the best.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of NO 3 − was delayed until day 14 in the Cu 2+ ‐treated soils. Using identical coating techniques, researchers achieved 12% and 8% reductions in NH 3 loss (compared to uncoated urea) using CuSO 4 and a mixture of CuSO 4 and ZnSO 4 , respectively (Babar et al., 2016; Junejo et al., 2013). In another study, amending pyrite‐coated and KCl‐coated urea products with CuSO 4 was shown to further reduce NH 3 loss by 4% (Damodar Reddy & Sharma, 2000).…”
Section: Introductionmentioning
confidence: 99%